Cognitive-behavioral modification to enhance academic self-efficacy: A case of junior high school students - Wicaksono, Luhur; Suharto, Suharto; Suryadi, Suryadi; Michael, Michael; Sulastri, Endang (UIN Raden Mas Said Surakarta, 2024)
Academic self-efficacy (ASE) is a critical determinant of students' success, yet traditional punishment-based approaches to counseling have proven ineffective in enhancing ASE. This study aimed to evaluate the effectiveness of Cognitive-Behavioral Modification (CBM) counseling in improving ASE among junior high school students. A quantitative research design was employed, utilizing a true experimental approach with a pretest-posttest control group design. Participants consisted of junior high school students from SMP Negeri 2 Malang, East Java province of Indonesia, who were randomly assigned to experimental and control groups. The experimental group received CBM counseling with a Modeling (M) technique, while the control group followed standard counseling practices. Data were collected using ASE assessments administered before and after the intervention, and analyzed using non-parametric statistical tests. Results demonstrated that CBM-M counseling significantly enhanced students' ASE compared to the control group. The findings suggest that the CBM approach, particularly when combined with modeling techniques, is highly effective in fostering positive cognitive and behavioral changes that improve ASE. These results emphasize the need for a shift from punishment-based strategies to problem-solving approaches in school counseling, with implications for broader educational practices.